Bolnik z rakom in njegov družinski zdravnik - Božiček, Franc (Obzornik zdravstvene nege, 1998)
The article describes the treatment for a cancer patient by a family physicianinto which also the patient's family is included. The physician should, apart from medical knowledge, exhibit also communication skills with his patient and his family. The article describes the optimum approach to the patient and his family, from the establishment of the diagnosis to patients's death.
Keywords: bolniki; družinska medicina; rak (medicina); zdravniki